TRANSFORMATIONAL LEADERSHIP IN ISLAMIC BOARDING SCHOOLS: STRATEGIES FOR IMPROVING STUDENT QUALITY - Alawiyah, Tuti; Gaffar, Andriana; Rosa, Ade Tutty Rokhayati (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Islamic boarding schools (pesantren) play a crucial role in shaping students' character and academic excellence. However, many pesantren face challenges in maintaining and improving student quality due to outdated leadership approaches, lack of innovation, and limited resources. This study examines the implementation of transformational leadership in Islamic boarding schools as a strategy to enhance student quality. The research aims to analyze the impact of transformational leadership on students' academic performance, character development, and overall competency. This study employs a qualitative research approach with a case study methodology, involving interviews, observations, and document analysis in selected pesantren. School leaders, teachers, and students participated as key informants to provide a comprehensive understanding of how transformational leadership influences educational outcomes. The findings indicate that transformational leadership significantly contributes to improving student quality by fostering a positive learning environment, encouraging teacher innovation, and enhancing student motivation. Leaders who inspire, mentor, and involve students in decision-making processes contribute to better academic achievement and character formation. However, challenges such as resistance to change, inadequate leadership training, and structural constraints still hinder the full implementation of transformational leadership. Based on these findings, the study recommends continuous leadership training programs, the integration of modern educational strategies with traditional pesantren values, and increased collaboration between pesantren and external stakeholders to ensure sustainable quality improvement. Future research could explore the long-term impact of transformational leadership in different pesantren models and its adaptability to diverse educational settings.